Luminosity Sensing Application of Negative Group Delay Predictor - Ravelo, Blaise; Guerin, Mathieu; Rajaoarisoa, Lala; Rahajandraibe, Wenceslas (IEEE transactions on industrial electronics (1982), 2024)
This article features on original application of negative group delay (NGD) predictor for the luminosity predetection. The low-pass (LP) type NGD prediction theory is established based on the time-advance consideration. The analytical design condition in function of expected prediction performance is formulated. The LP-NGD predictor is studied and characterized by using ramp signal input. The validity of the LP-NGD digital predictor with STM32 microcontroller implementation is verified by trapezoidal test signals having different rise/fall times and arbitrary waveform signal. Furthermore, excellent test result of real application is presented by using NLS-4942 luminosity photoresistor. An LP-NGD prediction demonstrator is designed and implemented with different time-advances (−30, −50, and −70 ms). The calculated and experimented results in good agreement show negative skew transient responses. The NGD predictor is potentially useful for industrial applications such as object detection, car safety, and smart building comfortability control system.